Indonesian Consumer Preference on Electric Motorcycle Design with Kansei Engineering Approach - Yoko Suparmadi; Slamet Riyadi; Deny Willy Junaidy (ITB Journal Publisher, LPPM ITB, 2021)
The Indonesian government is putting an effort into reducing the number of gasoline-fueled vehicles and replacing them with electric energy-based vehicles. This is stated in the General Draft of the National Energy Plan (RUEN), which is aimed at increasing the resilience of the national energy sector. Motorcycles are the largest contributor to the vehicle population in Indonesia at 82%. As the Indonesian government intends to stimulate the replacement of gasoline-fueled motorcycles by electric motorcycles, it is useful to conduct a study on the preferences related to motorcycle product designs among two-wheeled vehicle users in Indonesia. This study used the Kansei Engineering method to get a design direction as well as a factorial analysis for data result processing in order to obtain a unique design factor. The number of respondents in this study was 104 people from Jakarta and Bandung. The results of this study show that the respondents wanted an overall design that looks playful and masculine yet compact and active. In addition, the design has to have elements of a big scooter. This study was designed as an initial stage within the R & D process of electric motorcycle products and will be further developed in a follow-up study.